HUBUNGAN ANTARA KESIAPAN DENGAN KECEMASAN MAHASISWA DALAM MENGHADAPI PRAKTIK KEPENDIDIKAN TAHUN 2023: Indonesia, Inggris - Muhammad Nawawi; Amir Fatah (Journal of Automotive Technology and Education, 2025)
Abstract This study aims to identify the level of anxiety and readiness of students in facing the Teaching Practice and the relationship between these two variables among students of the Automotive Engineering Education Program at the Faculty of Engineering, Universitas Negeri Yogyakarta. The research employed a quantitative descriptive approach with the use of the Pearson product-moment correlation. The research population consisted of 51 students who were prospective participants in the 2023 Teaching Practice for the Automotive Engineering Education Program at the Faculty of Engineering, UNY. The findings of the research are as follows: (1) The majority of students (82.35%) have a high level of readiness in facing the 2023 teaching practice, with a small proportion (17.64%) having a very high level of readiness; (2) Most students (82.35%) have low levels of anxiety in facing the 2023 teaching practice, while there are some students (11.77%) with very low levels of anxiety and a small portion (5.88%) with high levels of anxiety; (3) There is a significant relationship between students' readiness and anxiety in facing the 2023 teaching practice, with a significance value of < 0.05 (0.000). The contribution of readiness to influencing students' anxiety in facing the 2023 teaching practice is 61.4%, while the remaining 38.6% is influenced by other factors not discussed in this study. The results indicate that if students' readiness increases, their anxiety levels tend to decrease, and vice versa. Keywords : Anxiety; Education Practice; Preparedness Abstrak Penelitian ini bertujuan untuk mengidentifikasi tingkat kecemasan dan tingkat kesiapan mahasiswa dalam menghadapi Praktik Kependidikan serta hubungan antar 2 variabel tersebut pada mahasiswa Program Studi Pendidikan Teknik Otomotif Fakultas Teknik Universitas Negeri Yogyakarta. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan menggunakan korelasi product moment. Populasi penelitian terdiri dari 51 mahasiswa calon peserta Praktik Kependidikan 2023 pada Program Studi Pendidikan Teknik Otomotif Fakultas Teknik UNY. Hasil penelitian menunjukkan bahwa: (1) Mayoritas mahasiswa (82,35%) memiliki tingkat kesiapan yang tinggi menghadapi praktik kependidikan 2023, dengan sebagian kecil (17,64%) memiliki tingkat kesiapan sangat tinggi; (2) Sebagian besar mahasiswa (82,35%) memiliki tingkat kecemasan yang rendah dalam menghadapi praktik kependidikan 2023, namun ada beberapa (11,77%) mahasiswa yang memiliki tingkat kecemasan sangat rendah dan sebagian kecil (5,88%) mahasiswa yang memiliki tingkat kecemasan tinggi; (3) Terdapat hubungan yang signifikan antara kesiapan dan kecemasan mahasiswa dalam menghadapi PK 2023, dengan nilai signifikansi < 0,05 (0,000). Sumbangan kesiapan dalam mempengaruhi kecemasan mahasiswa menghadapi PK 2023 adalah sebesar 61,4%, sementara 38,6% sisanya dipengaruhi oleh faktor lain yang tidak dibahas dalam penelitian ini. Hasil menunjukkan bahwa jika kesiapan mahasiswa meningkat, tingkat kecemasan mahasiswa cenderung menurun, begitu juga sebaliknya. Kata kunci : Kecemasan; Kesiapan; Praktik Kependidikan